A promising solution to the limits of microscopes for smooth surfaces: fluorophore-aided scattering microscopy. Issue 20 (6th April 2018) - Li, Liang; Liu, Jian; Liu, Yan; Liu, Chenguang; Zhang, He; You, Xiaoyu; Gu, Kang; Wang, Yuhang; Tan, Jiubin
Abstract : Reflected light escape and mesoscopic penetration are two serious problems for optical characterization using microscopes. Abstract : Reflected light escape and mesoscopic penetration are two serious problems for optical characterization using microscopes. For specular samples with steep slopes, the detector does not receive enough light and the detection algorithm is not be able to detect the peak position, and would generate non-measured points. Moreover, the mesoscopic penetration phenomenon has been ignored when measuring and observing the shapes of samples with multi-layer structures. But this phenomenon, due to the transparency of materials to certain wavelengths of light, may result in serious errors in the measurements of the heights of samples, as well as errors in the descriptions of their shapes. Here we describe the use of fluorophore-aided scattering microscopy to significantly extend the magnitudes of slopes that can be detected, and to essentially eliminate errors in measurements of height caused by mesoscopic penetration.